Optical Transitions Dominated by Orbital Interactions in Two-Dimensional Fullerene Networks - Haonan Bai; Xinwen Gai; Yi Zou; Jingang Wang (C)
Fullerenes are a class of highly symmetric spherical carbon materials that have attracted significant attention in optoelectronic applications due to their excellent electron transport properties. However, the isotropy of their spherical structure often leads to disordered inter-sphere stacking in practical applications, limiting in-depth studies of their electron transport behavior. The successful fabrication of long-range ordered two-dimensional fullerene arrays has opened up new opportunities for exploring the structure–activity relationship in spatial charge transport. In this study, theoretical calculations were performed to analyze the effects of different periodic arrangements in two-dimensional fullerene arrays on electronic excitation and optical behavior. The results show that HLOPC60 exhibits a strong absorption peak at 1050 nm, while TLOPC60 displays prominent absorption features at 700 nm and 1300 nm, indicating that their electronic excitation characteristics are significantly influenced by the periodic structure. Additionally, analyses of orbital distribution and the spatial electron density reveal a close relationship between carrier transport and the structural topology. Quantitative studies further indicate that the interlayer interaction energies of the HLOPC60 and TLOPC60 arrangements are −105.65 kJ/mol and −135.25 kJ/mol, respectively. TLOPC60 also exhibits stronger dispersion interactions, leading to enhanced interlayer binding. These findings provide new insights into the structural regulation of fullerene materials and offer theoretical guidance for the design and synthesis of novel organic optoelectronic materials.